PENGARUH PENDINGINAN UDARA DALAM PROSES PENCETAKAN TERHADAP MIKROSTRUKTUR BAJA COR STAINLESS TAHAN PANAS SS 309 - Pujadi, Pujadi; Irawan, Dimas (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
This research is designed to studythe microstructure properties of309 (HHtype) cast stainless steel.The materialwas manufacturedon an air cooling castingprocess. SS309 ACnotation is given to the materialto differ itfrom the same material made by mould cooling casting process (SS309 MC). The compositioncontrolduringcastingprocess has proven to ensurebothmaterials having austenitic structure. TheSS309 ACand SS309 MC austenite microstructure is stabilized with chromium carbide precipitate Cr7C3 aroundaustenite grain boundary and intergranullarly. However the optical microscope test showed the carbideprecipitate in SS309 AC is distributedmore homogenthan in SS309 MC. Thisstructure isfavorable for heatresistantcast stainless steel because it acts as austenite stabilizer in high temperature application. Thetensiletest shows that the SS 309 AC tensile strength (568.89 MPa) is qualified with the HH grade standard(550 MPa). This value is also better compared withSS309 MCtensile strength (543.9 MPa). TheSS309 MChas bigger carbideprecipitate grain size whichreduces its ductility.